(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The purpose of this study was to show that photographs have a psychological meaning, as people basically print and store the most significant photographs. And depending on the hierarchy of one’s own values, a person will store the corresponding photos. People choose those photographs where there are especially significant events or especially significant people. Therefore, in this way the psychological meaning is imposed on the photo. Learning person’s way of life in psychology can reveal psychological implementations, which are connecting personality with its necessities, values, and world views in general. And these psychological implications can be found in photographs of special personal importance. The most precious photos people have been keeping throughout their lives can be psychologically meaningful according to their values. This article details the experimental methods provided by the quality analysis. Since we are pre-limited by 10 pictures, we already have a psychological sense of them. The hierarchy of the selected pictures and the individual differences between the people also take an important place within the study.